Anti-N-Methyl-D-Aspartate-Receptor Encephalitis: A 10-Year Follow-Up - Meixensberger, Sophie; Tebartz van Elst, Ludger; Schweizer, Tina; Maier, Simon J.; Prüss, Harald; Feige, Bernd; Denzel, Dominik; Runge, Kimon; Nickel, Kathrin; Matysik, Miriam; Venhoff, Nils; Domschke, Katharina; et al. (Frontiers in Psychiatry, 2020)
Background: Anti-N-methyl-D-aspartate-receptor (NMDA-R) encephalitis is an autoimmune disease of the brain first described in 2007. The aim of this paper is to present a 10-year follow-up case history. Case presentation: The authors present the case of a 39-year-old female patient who developed an anti-NMDA-R encephalitis in 2009 with predominant severe catatonic symptoms. Anti-inflammatory therapy led to the disappearance of catatonic symptoms and was discontinued during the course of the disease. After acute therapy, the patient achieved an almost full recovery presenting with ongoing discrete symptoms of sensory overload, subtle cognitive deficits, and fatigue/reduced energy levels. The follow-up investigation in 2019 showed inconspicuous findings in laboratory diagnostics and magnetic resonance imaging. Electroencephalography (EEG) analysis using independent component analysis detected left hemispherical spike-wave complexes and intermittent slowing. Regarding the sensory overload and reduced energy level, the patient benefited from low-dose neuroleptics (risperidone, amisulpride). In terms of sensory overload associated with experiences of panic, cognitive deficits and coping with the disease, she improved with cognitive behavioral therapy (CBT). Conclusion: Anti-inflammatory treatment led to almost full recovery with persistent disappearance of catatonic symptoms; however, a dysexecutive syndrome led to ongoing relevant problems with good response to low-dose atypical neuroleptics and CBT. The patient had persistent EEG alterations that indicated continuing neuronal network instability. Therefore, the case demonstrates the importance of multidisciplinary outpatient treatment following acute therapy for anti-NMDA-R encephalitis in patients with ongoing psychiatric deficits. For the symptomatic treatment of executive dysfunctions, “classical” psychiatric treatment may be helpful in the course of the disease.